Comprehensive analysis of publications concerning combinations of immunotherapy and targeted therapies for hepatocellular carcinoma: a bibliometric study - Gan, Biling; Wu, Lei; Zhou, Shunan; Chen, Zhihong; Wu, Fan; Xu, Lianqun; Chen, Zhenrong; Ma, Honghui; He, Peijia; Fang, Dan; Shi, Ning (Frontiers in Immunology, 2025)
BackgroundHepatocellular carcinoma (HCC), a prevalent malignancy, is often diagnosed at advanced stages. Recent advances have integrated immunotherapy with targeted therapy, significantly improving treatment outcomes. This study provides a bibliometric overview of these therapeutic combinations, evaluating their development and impact.MethodsA rigorous selection process was applied to relevant literature from Web of Science, followed by in-depth bibliometric analyses— including timeline visualization, burst detection, and co-occurrence analysis—using CiteSpace and VOSviewer. This approach offered insights into the contributions of countries, institutions, authors, journals, references, and key terms within the field.ResultsA total of 506 studies published between 2014 and 2023 were included, with all articles in English. Mainland China dominated the publication output, contributing 40% (N = 202), followed by significant contributions from the United States and Japan. Kindai University led institutional contributions, accounting for 7.9% of the total (N = 40). The authors Kudo Masatoshi and Hatanaka Takeshi were the most prolific, each with nine publications. The journal Cancers emerged as the top publisher, with 48 relevant articles and an Impact Factor of 5.2 in 2022. A co-citation network analysis traced the evolution of immunotherapy and targeted therapy combinations in HCC treatment. Early research primarily focused on angiogenesis, dendritic cells, and expression markers, while recent trends have shifted towards phase III trials, adverse reactions, and checkpoint inhibitors, underscoring the field’s dynamic progression.ConclusionFuture research will expand on the pathological mechanisms underlying these therapies and novel interventions and combination strategies. Addressing adverse events and treatment discontinuation will remain central to advancing clinical applications.